Teknik pembentukan watak dalam pementasan projek teater Asylum / Burhanuddin Amir Hassan - Amir Hassan, Burhanuddin (Faculty of Film, Theatre and Animation, 2014)
This study examines the technique of developing a few characters in the staging project titled Asylum. By using the theory of acting, project aims to construct and develop more interesting and multi-dimensional characters. This study employs qualitative as its paradigm of research, with its methods being interview, observation, library and internet research. Therefore, this study draws on the 9 elements which are known as ‘The System’ introduced by Constantin Stanilavski. The findings of this study reveal that the actor has effectively applied the theory to his acting in the sense that the actor’s double performances (characters) have been easily distinguished and separately recognised.